YOGA AS A NON-PHARMACOLOGICAL INTERVENTION IN DISEASES - Dr. Abhay Shankaregowda (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
A paradigm change in healthcare has occurred recently, with an emphasis on investigating non-pharmacological interventions as supplements to traditional medical treatments. Of them, yoga has become one of the most effective and adaptable tools for managing a wide range of illnesses and fostering holistic well-being. Yoga, which has its roots in ancient India, is more than simply physical exercise; it’s a holistic approach to well-being that incorporates breathing exercises pranayama, physical postures asanas, mindfulness exercises, and meditation. Yoga’s ability to address the interdependence of mind, body, and spirit makes it a viable non-pharmacological intervention for managing disease. By taking a holistic approach, yoga aims to address underlying imbalances that lead to disease in addition to symptom relief. Because of its potential to enhance conventional medical treatments and promote general well-being, yoga has drawn the interest of researchers, patients, and healthcare professionals alike. Yoga’s appeal is due to its profound effects on mental and emotional health in addition to its physical advantages. Studies have indicated that yoga can improve mood, resilience, and general quality of life while lowering stress, anxiety, and depression. Furthermore, yoga’s focus on self-awareness and mindfulness encourages a closer relationship between the person and their inner experience, empowering them to manage health issues on their own